The use of social media in travel planning: Solutions for destination management organizations (DMOS) - Valente, Manuel Gaspar (2015)
Social media has been a widely discussed subject in the marketing and tourism literature. Even though most of tourism entities have adopted social media as marketing tool, its real potential and benefits still remain unclear for most of companies and businesses involved. Also, there is little evidence on the purposes of using social media in the travel planning and whether these platforms are relevant or not for companies to market their products and destinations. This project aims at understanding the role of social media in tourists’ travel planning while analyzing the current role of Destination Management Organizations (DMOs) in destination promotion. This study comprised a survey with 200 tourists visiting the city of Lisbon. It was examined their usage of social media in travel planning, sites content information and influence in their travel plans and destination image. The analysis suggests social media is a relevant source in tourists’ travel planning, providing a wide range of information and used throughout all travel planning stages. Also, research claimed social media content is perceived as trustworthy and it will influence tourists travel plans as well as tourists’ destination overall image. In addition, the current level knowledge and satisfaction with Portuguese DMOs social media sites content and features was also analyzed and further combined with a qualitative study of two DMOs interviews. This work provides insights of social media usage in the travel context and ultimately point solutions for DMOs to use them as a marketing tool. Given the fact this is one of the first studies analyzing Portuguese DMOs social sites, several recommendations are provided for future research.